2008
DOI: 10.1007/s12124-008-9066-7
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated View of Empathy: Psychology, Philosophy, and Neuroscience

Abstract: In this paper, we will examine and untangle a conflict mainly between a developmental psychologist, Martin Hoffman and a social psychologist, Daniel Batson. According to Hoffman, empathic distress, a vicarious feeling through empathy, is transformed into an altruistic motivation. Batson and others on the other hand, criticize Hoffman, claiming that empathic altruism has no relation with empathic distress. We will point out some problems with Batson's position by referring to the results of fMRI experiments tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…While the distinction concerning compassion is less clear one suggestion is that compassion is a higher order construct, consisting of feelings of sympathy and pity (Goetz et al, 2010). As such terms are more concerned with one’s feelings towards the other’s plight, rather than the sharing of emotions, they are more closely related to sympathy than empathy (Kalawski, 2010; Lishner et al, 2011; Nakao & Itakura, 2009).…”
Section: Distinguishing Empathy From Other Conceptsmentioning
confidence: 99%
“…While the distinction concerning compassion is less clear one suggestion is that compassion is a higher order construct, consisting of feelings of sympathy and pity (Goetz et al, 2010). As such terms are more concerned with one’s feelings towards the other’s plight, rather than the sharing of emotions, they are more closely related to sympathy than empathy (Kalawski, 2010; Lishner et al, 2011; Nakao & Itakura, 2009).…”
Section: Distinguishing Empathy From Other Conceptsmentioning
confidence: 99%
“…Developmental neuroimaging studies have suggested that the transition from an egoistic form of empathy in young children to a more reciprocal concern for other people in adulthood [18,19] is driven by the development of brain areas which support mentalizing [20,21]. For example, it was previously shown that bilateral TPJ was more active in response to different mental states in adults compared to children [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Interpersonal relationships are mediated by the empathetic knowledge structures people hold about themselves or infer about others (Nakao and Itakura, 2009). That is, a person's self-concept impacts how she or he perceives interpersonal knowledge, what people believe or feel regarding someone else, and influences how that person interacts with other people.…”
Section: Literature Reviewmentioning
confidence: 99%